Sahala in Digital Era: Artificial Intelligence and the Future of Batak Church Leadership - Siagian, Riris Johanna; Limbong, Sukanto (International Journal of Artificial Intelligence Research, 2024)
The objective of this study is to show that a deeper comprehension of Sahala, its cultural background, and Batak church leadership will provide insights into the various potential impacts of integrating sensors and algorithms into sociocultural practices. This study employed a qualitative research approach and descriptive methods. The choice of a qualitative paradigm is based on the study's aim to investigate and describe the identified issues, specifically the functions of the church leader and the church through Sahala. The purpose of qualitative research is to provide an in-depth analysis or description of a phenomenon, drawing from the significance derived from observed occurrences. This research reveals evolving church leadership dynamics in the age of artificial intelligence. As technology advances rapidly, church leaders must demonstrate adaptability and situational awareness. They need to modify their leadership approaches to strike a balance between traditional and modern methods. The study also underscores the necessity of ethically incorporating Sahala into AI systems. When considering the use of AI to integrate Sahala into genetic parenting, it is crucial to ensure that the technology respects traditions and has the potential to foster the development of genuine individuals. Moreover, community involvement is essential to incorporate their viewpoints into the technology's development process. Technologies that disregard community input pose significant moral risks, which can only be properly evaluated and mitigated through active engagement with the community